Classifying and resolving ambiguities in sketch-based interaction. (8th March 2010) - Avola, Danilo; Caschera, Maria Chiara; Ferri, Fernando; Grifoni, Patrizia
Natural interaction approaches, such as the Sketch-based interaction, frequently imply ambiguities in the interpretation by the computer side. This paper focuses only on micro-level ambiguity analysing the interpretation of the abstract geometrical elements point, polyline and polygon. Considering a dynamic perspective, ambiguities can be caused by: inaccuracy in the user's drawing, approximation of the represented reality and user's deletion or retracing of fragments of the sketch. Moreover, this paper discusses methods to solve ambiguities taking into account the spatial and temporal information that characterise the user's drawing, deleting and over-tracing process according to some experimental observations of users' behaviour.